Simulation study of wireless body sensor network - Fan, Yuqi (2014)
Wireless sensor networks (WSNs) and body area networks (BANs) are significant and popular technologies today. They can support a lot of applications in various areas, such as military, healthcare use and so on. In this report, the two technologies are reviewed and one simulation of BANs is run with the simulator Castalia. The most important objective of this project is to introduce the simulator Castalia to more undergraduate students whose majors are communication engineering.